2014
DOI: 10.3810/hp.2014.04.1105
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalist Management of Vaso-Occlusive Pain Crisis in Patients With Sickle Cell Disease Using a Pathway of Care

Abstract: Hospitalist-led management of patients with SCD VOCs using a care pathway that emphasizes early, aggressive PCA-based pain control is associated with reduced hospital LOS. The LOS reduction seen in our study is clinically meaningful. Notably, other measures of patient outcomes and quality of care metrics did not change significantly, and some trended towards improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…This argument is further supported by results obtained by Jayaram et al, 13 who observed significantly improved ordering of IS, but no effect on ACS incidence following implementation of a CPW that did not mandate IS use. The lack of a significant decrease in the percentage of patients transfused PRBCs is consistent with results obtained by Liles et al, 21 but contrasts with results obtained by Jayaram et al, 13 possibly because of either variability in CPW design or higher disease severity in the post-CPW implementation group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This argument is further supported by results obtained by Jayaram et al, 13 who observed significantly improved ordering of IS, but no effect on ACS incidence following implementation of a CPW that did not mandate IS use. The lack of a significant decrease in the percentage of patients transfused PRBCs is consistent with results obtained by Liles et al, 21 but contrasts with results obtained by Jayaram et al, 13 possibly because of either variability in CPW design or higher disease severity in the post-CPW implementation group.…”
Section: Discussionsupporting
confidence: 88%
“…Results from previous CPW studies for vaso-occlusive pain also support the notion that readmission risk among patients with SCD depends on access to outpatient health care. The CPWs developed and studied by Liles et al 21 and Co et al, 9 which did not incorporate interventions to improve discharge planning, did not observe a significant effect on readmission rate, whereas the CPW of Frei-Jones et al, 22 which specifically addressed discharge planning, observed a significant reduction in 30-day readmission rate. Explanations for the CPW's lack of effect on hospital LOS include higher disease severity in the post-CPW implementation study group and the absence of interventions available for vaso-occlusive pain management that have been shown to independently reduce hospital LOS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…secondary ACS) ranges from 12.5% to 42%, and the median time to onset is usually between 2-4 days. 3,4,[16][17][18][19][20] However, data on early-onset ACS (i.e. onset less than 24 hours (h) after the VOC) are particularly scarce, and it is not known whether early-onset ACS and secondary ACS have different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies have shown that utilization of a standard care pathway for all sickle cell patients leads to an increased use of PCAs but also a decrease in total length of stay. 6 Conti and colleagues 7 proposed an oral morphine regimen in an emergency department (ED) setting where IV meperidine had previously been used. They reviewed the ED visits of 9 patients prior to the implementation of the oral morphine protocol and after and noted a statistically significant decrease in total ED visits, length of stay, and number of admissions after the implementation of the oral protocol.…”
Section: Introductionmentioning
confidence: 99%